Safety and tolerability of intradermal influenza vaccination in patients with cardiovascular disease - Arintaya Phrommintikul (2018)
Background: It is well-established that influenza vaccination reduces adverse cardiovascular outcomes in patients with cardiovascular diseases (CVD), however, the vaccine coverage rate in most countries remains low. The concern about the local adverse effects of intramuscular injection, particularly in CVD patients receiving antithrombotic therapy, is one of the important impediments. This study was conducted to assess the safety, side effects and tolerability of intradermal influenza vaccine in CVD patients. Methods: This was an observational study in adult CVD patients who had undergone vaccination against seasonal influenza by intradermal vaccination between May 16th and May 30th, 2012 at Maharaj Nakorn Chiang Mai Hospital. The medical history, patients' acceptability and adverse effects were collected using a written questionnaire completed by the patient immediately following vaccination and by a telephone survey eight days later. Results: Among 169 patients, 52.1% were women and the mean age was 63 ± 12 years. Coronary artery disease, valvular heart disease and dilated cardiomyopathy were present in 121 (71.6%), 40 (23.7%) and 8 (4.7%), respectively. Antithrombotics were used in 89.3%. After vaccination, the pain score was 0, 1 or 2 (out of 10) in 44.4%, 15.1%, and 27.6% of the patients, respectively. Eight days after vaccination, the common adverse reactions were itching 19 (11.9%), swelling 9 (5.7%) and fatigue (4.7%). No hematoma or bruising was reported. Conclusions: The intradermal influenza vaccination is safe and well tolerates with high rates of satisfaction in CVD patients. This technique should be useful in expanding influenza vaccine coverage. ©2014 JGC All rights reserved.